Examining Genetic Variation in Maize Inbreds and Mapping Oxidative Stress Response QTL in B73-Mo17 Nearly Isogenic Lines - Sorgini, Crystal A.; Barrios-Perez, Ilse; Brown, Patrick J.; Ainsworth, Elizabeth A. (Frontiers in Sustainable Food Systems, 2019)
Screening crop plants under elevated ozone concentrations ([O3]) is a pre-requisite for identification of tolerant lines, but few studies have mapped maize responses to elevated [O3]. B73-Mo17 nearly isogenic lines (NILs) were screened in the field under ambient ( 40 ppb) and elevated ( 100 ppb) [O3] at the Free Air gas Concentration Enrichment (FACE) research facility in Champaign, IL to identify maize leaf damage QTL associated with variation in O3-induced oxidative stress response. In Mo17 NILs, a significant leaf damage QTL was identified at 161Mb on chromosome 2. To assess the feasibility of high-throughput phenotyping and fine mapping of early season O3 leaf damage QTL, a subset of the nested association mapping founder lines were screened in a growth chamber experiment under ambient and elevated [O3]. Results showed that elevated [O3] decreased the number of green leaves while increasing the number of lesioned and dead leaves. Most lines showed the same general response to elevated [O3], but the degree of damage varied among lines. Next, tolerant and sensitive B73-Mo17 NILs identified from the FACE study, and hybrid crosses of the identified NILs with Mo17 (n= 20) were grown under elevated O3 ( 150 ppb) in growth chambers (n=7). In the chambers, O3-sensitive lines could be distinguished from tolerant lines based on leaf lesions, but there was not a continuous degree of damage like that seen in the field. This research identified a repeatable O3-induced leaf damage QTL and developed populations and markers that can be used in future growth chamber fine mapping experiments. These results demonstrate the feasibility of high-throughput phenotyping and fine mapping of O3 leaf damage QTL in a controlled environment.